Aspectos epidemiológicos da esquistossomose em trabalhadores rurais sem terra no estado de Sergipe - Santos, Genilde Oliveira dos (2010)
Schistosomiasis is a water-borne disease caused by Schistossoma Mansoni and its clinical evolution can vary from asymptomatic forms to severe conditions. Schistosomiasis mansoni is a global endemic disease, occurring in 74 countries and territories of three continents. To verify through a parasitological examination of fecal samples the occurrence of Schistossoma Mansoni among landless rural workers and their families in settlements in riverside cities from the south region of the State of Sergipe. Materials and Methods: It is a quantitative cross-sectional approach study conducted on landless rural workers from the south region of the State of Sergipe. A physical examination was performed on 822 landless rural workers and 601 of them had a parasitological examination of fecal samples to confirm the infection. A 4.3 % prevalence of Schistosomiasis among landless rural workers was found with a positive result for the infection in 61.5 % among the 13 settlements studied. In a 100% of positive cases the clinical form of the disease found was the chronic intestinal. The population portrayed is a low-income community, living in floor soil ground four-room households (living-room, bedroom, bathroom and kitchen). The literacy level in these communities is low. In these populations 73.3% of the citizens had attended elementary school, 16.3 % of them are illiterate and 10 10.4% attended high school or higher education. In all the settlements there is poor sanitary condition, no tap water and sewer system. Occurrences of Schistosomiasis mansoni were evidenced in 8 (61.5%) of the Landless Rural Workers settlements studied and 26 (4.3%) of them had a positive result for the disease, although the prevalence of Schistosomiasis among landless rural workers from the south region of the State of Sergipe is relatively low in comparison to the whole state rates and in some cases from the south region. The predominant form of the disease is the chronic intestinal possibly due to the short period of exposure to this environment and to the characteristics of the migratory population. The socio environmental condition of the population is practically the same: low literacy level, predominance of rural work, lack of sanitation or sewer system and few of the rural workers have access to tap water. It was evidenced a very distinct prevalence between the settlements despite the resemblance of the socio environmental conditions, possibly due to differences concerning the deposit water to which this population is currently exposed.